The Effect of Strategic Management Accounting, Green Accounting, and Firm Age on Profitability with Company Size as a Moderating Variable in Energy Companies on the IDX for the 2020–2025 Period: Pengaruh Strategic Management Accounting, Green Accounting dan Firm Age terhadap Profitabilitas dengan Ukuran Perusahaan sebagai Variabel Moderasi pada Perusahaan Energi di BEI Periode 2020–2025 - Mahzumi, Ari Zidan; Darmayanti, Novi; Kusmayasari, Dewi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The energy sector faces increasing environmental regulatory pressure and sustainability demands that require more adaptive accounting strategies to maintain financial performance. Specific Background This study examines Strategic Management Accounting, Green Accounting, and Firm Age as determinants of profitability, measured by Return on Assets, with Firm Size positioned as a moderating variable in energy companies during the 2020–2025 period. Knowledge Gap Previous studies have produced inconsistent findings on the relationship between Green Accounting and profitability, while Firm Size has commonly been treated as a control variable rather than a contingency factor. Aims This study aims to empirically analyze Strategic Management Accounting, Green Accounting, and Firm Age in relation to profitability and assess the moderating role of Firm Size. Results The findings show that Strategic Management Accounting, Green Accounting, and Firm Age have positive and significant relationships with profitability. Firm Size strengthens the relationship between Strategic Management Accounting and profitability, as well as between Firm Age and profitability, but does not moderate the relationship between Green Accounting and profitability. Novelty The study offers an integrative model combining accounting strategy, environmental accounting, organizational maturity, and company scale in explaining profitability in the energy sector. Implications The findings indicate that energy companies should optimize Strategic Management Accounting and Green Accounting while considering organizational scale and maturity to sustain profitability under energy transition pressure. Highlights • Strategic Management Accounting shows a positive and significant relationship with profitability.• Green Accounting contributes significantly through environmental cost internalization and operational efficiency.• Firm Size moderates Strategic Management Accounting and Firm Age, but not Green Accounting. Keywords Strategic Management Accounting; Green Accounting; Firm Age; Firm Size; Profitability